APPLICATION OF WEARABLES AND TELEREHABILITATION FOR MONITORING AND REHABILITATION OF DEGENERATIVE CHRONIC LOW BACK PAIN (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize evidence on the effectiveness and implementation of wearable devices and telerehabilitation for monitoring and rehabilitation of chronic low back pain due to degenerative causes, including impacts on pain, disability, adherence, and safety.Methods: We searched PubMed and major rehabilitation/spine journals (2019-2025) for randomized trials, systematic reviews and guidelines about exercise-based telerehabilitation, remote monitoring with inertial and physiological sensors, and digital care pathways for chronic low back pain. Data were narratively synthesized by domains: clinical effectiveness, adherence/engagement, safety and adverse events, and implementation considerations.Results: Recent randomized and network meta-analytic evidence indicates that telerehabilitation programs delivering structured exercise and education are non‑inferior to in‑person care for pain and disability in chronic low back pain, with small to moderate improvements versus minimal care and comparable adverse‑event profiles. Wearables (e.g., IMU posture/activity trackers) enable objective monitoring of mobility and home‑exercise adherence and can personalize feedback, though measurement heterogeneity and usability barriers persist. Professional guidelines endorse exercise and self‑management as first‑line care; telerehabilitation aligns with these principles and global digital‑health recommendations when implemented with attention to equity, privacy and data security.Conclusion: For degenerative chronic low back pain, telerehabilitation augmented by wearables is a feasible, effective option to scale guideline‑concordant care and support long‑term self‑management. Standardization of sensor metrics, reporting of engagement, and pragmatic trials in low‑ and middle‑income settings are priorities for future research.
Keywords: Chronic low back pain, telerehabilitation, wearable sensors, digital health, remote monitoring.